Myocardial Fibrosis Predicts 10-Year Survival in Patients Undergoing Aortic Valve Replacement. (August 2018) - Herrmann, Sebastian; Fries, Bastian; Salinger, Tim; Liu, Dan; Hu, Kai; Gensler, Daniel; Strotmann, Jörg; Christa, Martin; Beer, Meinrad; Gattenlöhner, Stefan; Störk, Stefan; Voelker, Wolfram; et al.
Abstract : Background: Long-term data on evolution and clinical impact of myocardial fibrosis in valvular heart disease are scarce. Methods and Results: In this 10 years' extension of a prospective study in patients undergoing conventional aortic valve replacement because of symptomatic severe aortic valve stenosis, the impact of myocardial replacement fibrosis (MRF) on long-term outcome was assessed. Endomyocardial biopsies were acquired during aortic valve replacement in 58 consecutive patients. MRF was graded using the calculated percentage area of fibrosis and patients categorized as severe (n=21), mild (n=15), and no fibrosis (n=22). Echocardiography including strain imaging, as well as cardiovascular magnetic resonance, to assess late gadolinium enhancement was performed at baseline, 1, and 10 years after aortic valve replacement. Death of any cause occurred in 21 patients (38.9%): 3 (14.3%) in the group without MRF, 6 (42.9%) in the mild MRF group, and 12 (63.2%) in the severe MRF group ( P =0.006), resulting in the lowest cumulative survival for patients with severe MRF (log-rank P =0.003). In the group without MRF, none died of cardiovascular cause. MRF was found to be an independent predictor of survival (hazard ratio, 1.271; 95% CI, 1.032–1.564; P =0.024). Conclusions: This 10-year follow-up study underlines the profound impact of replacement fibrosis with regard to cardiac and all-cause mortality in patients undergoing aortic valve replacement for severe aortic valve stenosis. Integrating cardiovascular magnetic resonance and echocardiographic functional imaging beyond ejection fraction quantification could help in clinical decision making to stratify patient prognosis with regard to myocardial longitudinal function and prevalence of replacement fibrosis.